Abnormal Skin Conditions (Skin Disorders) in Babies Aged 0-12 Months Regarding the Use of Tools to Maintain the Cleanliness and Comfort of Babies (Baby Diapers) And Mother's Behavior In Tangkil Village - Putri, Maidina; Pannyiwi, Rahmat; Nurhaedah, Nurhaedah; Treasa, Adisty Dwi; Leli, Leli; Lubis, Halimatussakdiyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Babies have very sensitive skin, different from adult skin, which makes babies more susceptible to infection, irritation, and allergies, and it is not uncommon for babies to experience dermatitis, one of which is commonly called diaper dermatitis. Baby diapers are tools used and created to absorb urine and hold feces, designed to keep the skin dry so that it is protected from direct contact with the baby's clothes, bed and environment. The purpose of this study was to determine the relationship between the use of tools to maintain cleanliness and comfort of babies (baby diapers). This type of research is quantitative analytical. The population and sample of respondents were all babies aged 0-12 months who used baby diapers, totaling 64 people. The behavioral measurement method uses the scoring method and for data processing uses univariate and bivariate analysis. Data were analyzed descriptively in the form of tables and narratives. The results of the study showed that the level of maternal knowledge was good, the mother's attitude and actions were good. There was no significant relationship between maternal knowledge of skin disorders in infants (p value = 0.648), there was no significant relationship between maternal attitudes towards skin disorders in infants (p value = 0.256), but there was a significant relationship between maternal actions towards skin disorders in infants (p value = 0.045).